Antifreeze Proteins in the Arctic Shorthorn Sculpin (Myoxocephalus scorpius) - Fletcher, Garth L.; Addison, Richard F.; Slaughter, Don; Hew, Choy L. (ARCTIC, 1982)
The plasma of shorthorn sculpin caught at Grise Fiord (Southern Ellesmere Island, arctic Canada) during late August contained antifreeze proteins which were essentially identical, with respect to molecular weight, number of components and amino acid composition, to the antifreeze proteins found in Newfoundland populations of shorthorn sculpin. The concentration of antifreeze protein in the plasma of the arctic sculpins during the summer was similar to that observed in the plasma of Newfoundland sculpin during the winter. The results suggest that unlike their Newfoundland counterparts, the plasma of sculpin residing in the High Arctic contains high concentrations of antifreeze protein all year round.Key words: shorthorn sculpin, Myoxocephalus scorpius, antifreeze proteins